KIND snacks: the difference between nice and kind - Neisser, Drew (Henry Stewart Talks, 2018)
This case study describes the journey of KIND Snacks founder and CEO, Daniel Lubetzky, through his first unsuccessful business venture, to his current, successful company and global programme to encourage acts of kindness while promoting healthy eating.